Crystal structures of full length DENV4 NS2B-NS3 reveal the dynamic interaction between NS2B and NS3 - Phoo, Wint Wint (2022)
Flavivirus is a genus of the Flaviviridae family which includes significant emerging and re-emerging human disease-causing arboviruses such as dengue and Zika viruses. Flaviviral non-structural protein 3 (NS3) protease-helicase plays essential roles in viral replication and is an attractive antiviral target. A construct which connects the cytoplasmic cofactor region of NS2B and NS3 protease with an artificial glycine-rich flexible linker has been widely used for structural, biochemical and drug-screening studies. The effect of this linker on the dynamics and enzymatic activity of the protease has been studied by several biochemical and NMR methods but the findings remained inconclusive. Here, we designed and carried out a comparative study of constructs of NS2B cofactor joined to the full length DENV4 NS3 in three different ways, namely bNS2B47NS3 (bivalent), eNS2B47NS3(enzymatically cleavable) and gNS2B47NS3 (glycine-rich linker). We report the crystal structures of linked and unlinked NS2B47-NS3 constructs in their free state and in complex with bovine pancreatic trypsin inhibitor (BPTI). These structures demonstrate that the NS2B cofactor predominantly adopts a closed conformation in complex with full-length NS3. The glycine-rich linker between NS2B and NS3 may promote the open conformation which interferes with protease activity. This negative impact on the enzyme structure and function is restricted to the protease activity as the ATPase activity is not affected in vitro.